Problems and Solutions in Rice Production and Marketing in Takhar Province of Afghanistan - Alamyar, Roohullah; Boz, Ismet (International Journal of Scientific Research and Management (IJSRM), 2018)
Agriculture is a critical sector for Afghanistan. About 70 percent of the population lives in rural areas and works on farms. Naturally, the Afghan economy is focused on the agricultural sector. But the agrarian infrastructure encountered significant damage during the 30-year war. Before the war in the 1970s, Afghanistan was an international supplier of agricultural products and 48% of the export revenue was obtained from these products. Rice consumption is mainly dependent on rice imports to meet the growing demand of Afghanistan's growing population due to the livelihood and semi-subsistence rice farming and the continuity of low-quality of local rice varieties. On average, the country imported about 218 million tonnes of rice each year in the 2014-2017 period, accounting for about $70 million (approximately 1.4% of the agricultural GDP). For Afghanistan to meet rice demand with domestic production, it is recommended to adopt highly productive seed varieties, relevant inputs, and sustainable farm management practices.